Pengaruh MMA terhadap Citra Rusia dalam Olahraga Seni Beladiri Internasional 2012-2021 - Nugraha, Raditya Abdurrahman (Global and Policy Journal of International Relations, 2023)
Abstract Sport has become one of the influential instruments for the image of a country. Russia as an influential country in the world, is also famous for using sports as a political tool for its foreign cooperation. The popularity of mixed martial arts events or MMA in the world, makes the Russian fighter to be reckoned with because of his dominance over his victories. This is followed by the background of the Russian president, Vladimir Putin, who pays special attention to the sport of martial arts in Russia. The presence of the Russia MMA Union in 2012, was the starting point for the dynamics between international MMA organizations such as UFC, Bellator, and M-1 Global as a collaboration to improve Russia's image in international martial arts sports. In addition, the use of MMA athletes through sportswashing was also carried out by Vladimir Putin in improving the image of the Russian state. Thus, there is a dynamic associated with governmental and non-governmental actors, to improve the image of the Russian state in the international public with the sport of MMA. The author will explain the Influence of MMA on the Image of Russia in International Martial Arts Sports 2012-2021. Keywords: Sports, Image, Mixed Martial Arts, Sportswashing, Russia.   Olahraga telah menjadi salah satu instrumen yang berpengaruh bagi citra suatu negara. Rusia sebagai negara yang berpengaruh di dunia, juga terkenal dengan menggunakan olahraga sebagai alat politik terhadap kerjasama luar negerinya. Popularitas ajang seni beladiri mixed martial arts atau MMA di dunia, menjadikan petarung Rusia diperhitungkan karena dominasi atas kemenangannya. Hal ini diikuti dengan latar belakang presiden Rusia, Vladimir Putin, yang memberikan perhatian khusus bagi olahraga seni beladiri di Rusia. Kehadiran Russia MMA Union di tahun 2012, merupakan titik awal dari dinamika antar organisasi MMA internasional seperti UFC, Bellator, dan M-1 Global sebagai kerjasama meningkatkan citra Rusia dalam olahraga seni beladiri internasional. Selain itu, penggunaan atlet MMA melalui sportswashing juga dilakukan Vladimir Putin dalam meningkatkan citra negara Rusia. Dengan demikian, terdapat dinamika yang berhubungan antara aktor pemerintah dan non-pemerintah, untuk meningkatkan citra negara Rusia di publik internasional dengan adanya olahraga MMA. Penulis akan menjelaskan Pengaruh MMA terhadap Citra Rusia dalam Olahraga Seni Beladiri Internasional 2012-2021. Kata kunci: Olahraga, Citra, Mixed Martial Arts, Sportswashing, Rusia.DOI: https://doi.org/10.33005/jgp.v11i01.3393